Automatic 3D CT liver segmentation based on fast global minimization of probabilistic active contour. Issue 4 (13th December 2022) - Jin, Renchao; Wang, Manyang; Xu, Lijun; Lu, Jiayi; Song, Enmin; Ma, Guangzhi
Abstract: Purpose: Automatic liver segmentation from computed tomography (CT) images is an essential preprocessing step for computer‐aided diagnosis of liver diseases. However, due to the large differences in liver shapes, low‐contrast to adjacent tissues, and existence of tumors or other abnormalities, liver segmentation has been very challenging. This study presents an accurate and fast liver segmentation method based on a novel probabilistic active contour (PAC) model and its fast global minimization scheme (3D‐FGMPAC), which is explainable as compared with deep learning methods. Methods: The proposed method first constructs a slice‐indexed‐histogram to localize the volume of interest (VOI) and estimate the probability that a voxel belongs to the liver according its intensity. The probabilistic image would be used to initialize the 3D PAC model. Secondly, a new contour indicator function, which is a component of the model, is produced by combining the gradient‐based edge detection and Hessian‐matrix‐based surface detection. Then, a fast numerical scheme derived for the 3D PAC model is performed to evolve the initial probabilistic image into the global minimizer of the model, which is a smoothed probabilistic image showing a distinctly highlighted liver. Next, a simple region‐growing strategy is applied to extract the whole liver mask from the smoothed probabilistic image. Finally, a B‐spline surface is constructed to fit the patch of the rib cage to prevent possible leakage into adjacent intercostal tissues. Results: The proposed method is evaluated on two public datasets. The average Dice score, volume overlap error, volume difference, symmetric surface distance and volume processing time are 0.96, 7.35%, 0.02%, 1.17 mm and 19.8 s for the Sliver07 dataset, and 0.95, 8.89%, − 0.02 % -0.02%, 1.45 mm and 23.08 s for the 3Dircadb dataset, respectively. Conclusions: The proposed fully‐automatic approach can effectively segment the liver from low‐contrast and complex backgrounds. The quantitative and qualitative results demonstrate that the proposed segmentation method outperforms state‐of‐the‐art traditional automatic liver segmentation algorithms and achieves very competitive performance compared with recent deep leaning‐based methods.